Who Maintains “Old England”? - Tourism and Migration in the English Countryside - Yuko Shioji (Via@)
The imaginary world of “Old England” has attracted tourists and incomers to the English countryside since the 19th century. This has had a great impact on the local community. This paper is a case study of a country town in the Cotswolds. It describes the local community and their reactions to tourism and migration, and highlights the prominent role played by incomers in maintaining the imaginary world which drew them to the town. This paper also looks at how local people have worked to uphold the legacy of their ancestors.